2018
DOI: 10.22196/rp.v20i43.3844
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida docente: relação entre alterações psicoemocionais e disfonias

Abstract: RESUMO: o presente estudo se propõe a compreender os impactos das alterações psicoemocionais dos educadores, no desencadeamento de disfonias e seus aspectos relacionados à qualidade de vida do portador, considerando a relação existente entre saúde vocal, estado emocional e condições de trabalho. trata-se de uma revisão bibliográfica em diferentes bases de dados, da qual emergiram os seguintes temas: saúde vocal na docência; reflexos dos aspectos psicoemocionais nas disfonias; e, repercussão das alterações voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, to date, no studies have been found associating these two factors. Nevertheless, some previous studies with teachers already indicated that aspects related to mental disorders were associated with other variables (5,35) , which suggests greater attention to the psycho-emotional conditions of these workers.…”
Section: Discussionmentioning
confidence: 90%
“…However, to date, no studies have been found associating these two factors. Nevertheless, some previous studies with teachers already indicated that aspects related to mental disorders were associated with other variables (5,35) , which suggests greater attention to the psycho-emotional conditions of these workers.…”
Section: Discussionmentioning
confidence: 90%